Design of a Drying Equipment Moringa Leaf with Utilizing Temperature Air Conditioning Condenser - Masykur, Masykur; Saputra, Maidi; Munawir, Al; Pribadyo, Pribadyo; Jalil, Muhammad; Muzakir, Muzakir; Yuvenda, Dori; Setiawan, M. Yasep; Y, Fadhil (Universitas Negeri Padang, 2023)
This study conducted to get drying equipment a moringa leaf using air temperature from an air conditioning condenser. The first steps taken were collecting research literature, formulating problems, and design a drying equipment moringa leaf (moringa oleifera) using air temperature from an air conditioning condenser. Drying equipment tool made from plywood, wood, aluminum foil, styrofoam, and pipe channel to drying equipment. It works by utilizing air from the air conditioning condenser which is channeled through a pipe channel to drying equipment. The test was carried with modification intake channel to drying equipment without suction fan and using suction fan. Data collection is carried out every 30 minutes for 7 hours which starting from 10.00 AM to 05.00 PM. A sample of 800 grams of wet moringa leaf was placed on each drying rack. The result study without suction fan in the drying equipment show average temperature air from the condenser of 31.17 °C, average humidity of 68.8%, and a reduction in water content of moringa leaf of 35.5%. Meanwhile, the test using an air suction fan in the drying equipment was average temperature air from the condenser 34.10 °C, average humidity was 62.30% and the reduction in water content of moringa leaf was 40.8%. The drying rate of moringa leaf in the test using an exhaust fan is 0.0138 kg/hour, while the drying rate of moringa leaf in the test without using an exhaust fan is 0.01 kg/hour.